Sociolinguistic Communicative Competence of Graduate English Language Education Students in Classroom Interactions - Pratiwi, Suciaty; Hasib, Mujib (Celebes Scholar pg, 2024)
The sociolinguistic communicative competence idea pertains to an individual's ability to proficiently comprehend, produce, and use language in a way that is congruent with the particular situation. Therefore, it is important to thoroughly examine the students' level of competency while they participate in classroom activities, especially throughout the process of engaging in conversations. The present study was carried out at Pascasarjana UNM, including a sample of English graduate students in their third semester. A single class consisted of a total of 25 pupils. The researcher used a discourse analysis methodology to examine and interpret the collected data. A comprehensive collection of six recordings was undertaken to document the students interactions throughout class, supplemented by an additional five recordings derived from the interview segments. Subsequently, the transcriptions underwent meticulous scrutiny and analysis, with a specific emphasis on the student’s sociolinguistic proficiency as outlined by Sato & McNamara (2019) in the context of speech actions. The findings unearthed a diverse array of sociolinguistic communicative ability among graduate students, including assertive force, directive force, commissive force, and expressive force. The students used their abilities to embrace their classmates, provide crucial information, inquire, articulate expectations, provide ideas, and condense the subject. Through the analysis of the functions, it was determined that students mostly used a directed approach, characterized by their reliance on questioning. This method was used 67 times, representing 28% of the overall usage. By comprehending the communication patterns of students, instructors may customize their approach and pinpoint efficacious learning tactics for each person.